Development of Android-based Augmented Reality Learning Media on Atomic Matter - Salimah Manah Kumalasari; Retno Aliyatul Fikroh* (Jurnal Pendidikan Sains Indonesia, 2023)
Material and limited chemistry learning media resulted in less than optimal student scores. Necessary to develop learning media that can support studying by utilizing technology. This study aims to determine the quality and develop android based augmented reality learning media on atomic material. The type of research used is development research with the 4-D model (define, design, develop, and disseminate, which is limited to the development stage. The product was validated by one media expert lecturer, one material expert lecturer, and three reviewers (senior high school teachers) and responded to by ten senior high school students. The instrument used was a product quality sheet with a Likert scale and a student response sheet with a Guttman scale. The product's characteristics developed in the form of an application with atomic materials, augmented reality cameras, and student quizzes. The results of the quality assessment by media experts got a percentage of 97.14%, by material experts got a percentage of 83.33%, and the reviewer got a percentage of 95.8% with a very good category. The product was responded to positively by students with a percentage of 99%. Based on these results, android-based augmented reality learning media on atomic material in senior high school can be used as an alternative learning media to increase student interest in learning chemistry